The Socpen and Its Role in Closing the Coverage Gap Among Poor Elderly Filipinos - Velarde, Rashiel B.; Albert, Jose Ramon G. (World Bank, Washington, DC, 2018)
Since the formulation of the Philippine Development Plan (PDP) of 2010-2016, social protection (SP) has figured more prominently in the country's development agenda and in policy dialogs. The PDP for 2017-2022 continues the same emphasis on SP (National Economic and Development Authority (NEDA), 2017a). For the first time, policies to achieve social protection for all Filipinos have been featured in the PDP, with the view to building resilience of Filipinos, their families and communities. Specific strategies include enhancing social protection for the informal sector, improving the social pension system, strengthening mechanisms to ensure enrolment in the social security system, expanding health insurance packages, establishing an unemployment insurance system, among others. Further, the PDP also highlights the requirements to address implementation issues on convergence, planning, mainstreaming of SP at the local level, including better M&E, collection and use of data. The